2023
DOI: 10.2174/1574887118666230118102252
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Agents for Preventing Cardiotoxicity Induced Following Anticancer Agents: A Systematic Review and Meta-Analysis of Clinical Trials

Abstract: Background: Anthracyclines can improve survival in many types of malignancies, but dose-dependent and irreversible results following the use of anthracyclines have been associated with cardiomyopathy. This meta-analysis aimed to compare the effects of prophylactic agents for preventing cardiotoxicity induced following anticancer agents. Methods: In this meta-analysis, Scopus, Web of Science, and PubMed were surfed for articles published by December 30th, 2020. The keywords were angiotensin‐converting enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…DOXIC is an important public health problem. Though some clinical trials have shown that non-drug interventions such as exercise, healthy lifestyle, control of risk factors and treatment of comorbidities, as well as pharmacologic interventions including blockers, angiotensin converting enzyme inhibitors, angiotensin receptor antagonists, statins, dexrazoxane and liposome preparations [ 10 , 11 , 12 ], have mitigated the effects of DOX, we are far from achieving a complete solution to this important problem. Hence, it is important to have a thorough understanding of its toxicity and mechanisms of action, in order to further develop novel therapeutics to avoid or mitigate the effects of DOX.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DOXIC is an important public health problem. Though some clinical trials have shown that non-drug interventions such as exercise, healthy lifestyle, control of risk factors and treatment of comorbidities, as well as pharmacologic interventions including blockers, angiotensin converting enzyme inhibitors, angiotensin receptor antagonists, statins, dexrazoxane and liposome preparations [ 10 , 11 , 12 ], have mitigated the effects of DOX, we are far from achieving a complete solution to this important problem. Hence, it is important to have a thorough understanding of its toxicity and mechanisms of action, in order to further develop novel therapeutics to avoid or mitigate the effects of DOX.…”
Section: Discussionmentioning
confidence: 99%
“…However, it still has some shortcomings: it can aggravate the bone marrow suppression caused by chemotherapy drugs, affect the antitumor effect of DOX, and may lead to secondary malignant tumors after long-term use [ 8 , 9 ]. Besides, some clinically available drugs including blockers, angiotensin converting enzyme inhibitors, angiotensin receptor antagonists, and statins have exhibited certain benefits in delaying the progression of heart failure induced by DOX [ 10 , 11 , 12 ]. However, these medications are not curative and there is still an urgent need to explore new strategies targeting the pathological mechanisms of DOXIC to develop more therapeutic strategies to prevent it in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been numerous studies on the treatment of cardiovascular diseases by DMY. A large number of studies [7][8][9] have shown that DMY can inhibit endothelial damage, participate in lipid metabolism and affect the process of atherosclerosis, regulate mitochondrial metabolism and functional changes of cardiomyocytes, and inhibit oxidative stress-induced apoptosis in the treatment of MIRI. However, DMY is poor in water solubility, unstable to light and heat, and low in bioavailability [10], which greatly hinders its application and development.…”
Section: Introductionmentioning
confidence: 99%